The Effect of Emotional Intelligence on Conflict Resolution Skills Mediated by Empathic Concern in Youth - Al-Taie, Zainab; Abdulhussein, Omar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the relationship between emotional intelligence and conflict resolution skills among youth, with empathic concern as a potential mediator, in order to better understand the mechanisms through which emotional competencies influence constructive conflict management. Methods and Materials: A descriptive correlational research design was employed with a sample of 415 youth from Iraq, selected according to the Morgan and Krejcie table. Data were collected using the Emotional Intelligence Scale (Schutte et al., 1998), the Empathic Concern subscale of the Interpersonal Reactivity Index (Davis, 1980), and the Conflict Resolution Skills Scale (Johnson & Johnson, 1996). Pearson’s product–moment correlation coefficients were calculated to assess bivariate associations between variables, and Structural Equation Modeling (SEM) was performed in AMOS 21 to test the hypothesized mediation model. Model fit was evaluated using χ²/df, GFI, AGFI, CFI, RMSEA, and TLI indices. Findings: Correlation analysis revealed significant positive associations between emotional intelligence and empathic concern (r = .56, p < .001), emotional intelligence and conflict resolution skills (r = .62, p < .001), and empathic concern and conflict resolution skills (r = .58, p < .001). The SEM demonstrated excellent model fit (χ²/df = 1.38, GFI = 0.96, AGFI = 0.94, CFI = 0.98, RMSEA = 0.031, TLI = 0.97). Emotional intelligence significantly predicted conflict resolution skills both directly (β = 0.44, p < .001) and indirectly through empathic concern (β = 0.21, p < .001), with the total effect being substantial (β = 0.65, p < .001). Conclusion: The results highlight emotional intelligence as a key determinant of effective conflict resolution among youth, with empathic concern serving as a significant mediator. These findings underscore the importance of integrating emotional and empathy training into educational and youth development programs to enhance interpersonal competencies and reduce destructive conflict behaviors.